The role of professional practices of primary school mathematics teachers in developing the skills of creative solution to mathematical problems among their students from the point of view of specialists - Al-Amary, Muhannad Muhammad (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the role played by the professional practices done by Mathematics teachers at primary schools in the development of students’ skills in solving Mathematics problems creatively from a professional point of view. In addition, the study aimed to identify any statistically significant differences in the professional practices according to some variants (job titles, years of experience, and qualifications). To achieve the objectives of the study, the researcher used the descriptive approach in surveys. A questionnaire has been designed as a tool to collect data. The questionnaire has been proved valid, reliable and practical when responded to by a sample included 80 Mathematics teachers and supervisors at Jeddah Directorate of Education (31) educational supervisors and (49) primary teachers. The questionnaire has been analyzed and statistically processed by SPSS. The research has formulated a list of professional practices done by Mathematics teachers at primary schools to develop students’ creativity skills in solving Mathematics problems, which all were of equal high importance and came in a descending order in three axes: understanding the problem, execution planning, and generating ideas. Also, the study found that there are statistically significant differences in the responses in average for the job title (educational supervisor, teacher) variant concerning the role played by Mathematics teachers at primary schools in the development of students’ skills in solving Mathematics problems creatively in all axes and in the questionnaire as whole. In addition, there is a statistically significant difference at ≥α)0.05) between the averages of responses of professionals according to the qualifications and years of experience on the role played by Mathematics teachers at primary schools in the development of students’ skills in solving Mathematics problems creatively for both the understanding problems and generating ideas axes. There are not any statistically significant differences in the execution and planning axis. Hence, the study set a model proposal for the roles to be played and practiced professionally by Mathematics teachers at primary schools to develop students’ skills in solving Mathematics problems creatively. In the light of the study, the researcher introduced a set of recommendations and suggestions.
Keywords: Mathematics teachers; creativity skills in solving Mathematics problems; professional practices